2019
DOI: 10.35940/ijeat.f9504.088619
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Rear Under-Ride Protection Device (RUPD) During Car to Heavy Truck Rear Impact

Abstract: Abstract: Passenger vehicles crashes with Under-ride rear end of heavy vehicles result in fatal injuries due to sliding of passenger car beneath heavy trucks frames. This is related to an improper structure design of rear under-ride protection device (RUPD) that is mounted to the rear of the heavy vehicles. The design of effective RUPD must be taken into consideration during the design stage of truck chassis frame. There are two types of analyses used to investigate the performance of trucks RUPDs such as exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Regarding the potential design guideline, many studies [6][7][8] suggested that the energy absorption in underrun protective device can be used as assessment criteria of occupant injury level. Schram et al 6 investigated the possibilities to assess energy-absorbing front underrun protective devices with respect to injuries of the car occupant using numerical simulation, without a car and dummy in the test procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the potential design guideline, many studies [6][7][8] suggested that the energy absorption in underrun protective device can be used as assessment criteria of occupant injury level. Schram et al 6 investigated the possibilities to assess energy-absorbing front underrun protective devices with respect to injuries of the car occupant using numerical simulation, without a car and dummy in the test procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Schram et al 6 investigated the possibilities to assess energy-absorbing front underrun protective devices with respect to injuries of the car occupant using numerical simulation, without a car and dummy in the test procedure. Abid et al 7 applied explicit dynamic finite element (FE) method to model the impacting scenarios of a car and a truck. The study focused on the RUPD energy absorption and displacement of the impacting vehicle.…”
Section: Introductionmentioning
confidence: 99%